Promoting Mathematical Literacy for Digital Natives: Utilizing Technology in Elementary Mathematics Education - Caniago R.A; Maribot A.; Mendrofa G.K.H; Raihani S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The mathematical literacy skills of students in Indonesia are still low. This is something to be wary of, because even though the government has developed the curriculum and it is recorded that it has undergone three changes from 2000 – 2017, it turns out that not much has changed, especially in students' mathematical literacy skills. The low level of students' mathematical literacy skills is influenced by the low quality of mathematics teaching. Learning by utilizing technology can help make the learning process easier for students. This research utilizes the literature review method, namely examining relevant articles. The results of several studies show that the use of technology in mathematics learning has a positive impact on mathematical literacy competency skills. Thus, indirectly the use of technology in mathematics learning can improve students' mathematical literacy skills.